The interplay between the microbiota, diet and T regulatory cells in the preservation of the gut barrier in inflammatory bowel disease - Prame Kumar, Kathryn; Ooi, Joshua D.; Goldberg, Rimma (Frontiers in Microbiology, 2023)
Inflammatory bowel disease (IBD) is becoming more common in the Western world due to changes in diet-related microbial dysbiosis, genetics and lifestyle. Incidences of gut permeability can predate IBD and continued gut barrier disruptions increase the exposure of bacterial antigens to the immune system thereby perpetuating chronic inflammation. Currently, most of the approved IBD therapies target individual pro-inflammatory cytokines and pathways. However, they fail in approximately 50% of patients due to their inability to overcome the redundant pro inflammatory immune responses. There is increasing interest in the therapeutic potential of T regulatory cells (Tregs) in inflammatory conditions due to their widespread capability to dampen inflammation, promote